2008
DOI: 10.1111/j.1420-9101.2008.01609.x
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in parental care, habitat selection and larval life history between two species of Peruvian poison frogs: an experimental analysis

Abstract: Changes in the nature of the ecological resources exploited by a species can lead to the evolution of novel suites of behaviours. We identified a case in which the transition from large pool use to the use of very small breeding pools in neotropical poison frogs (family Dendrobatidae) is associated with the evolution of a suite of behaviours, including biparental care (from uniparental care) and social monogamy (from promiscuity). We manipulated breeding pool size in order to demonstrate experimentally that br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 33 publications
2
59
0
Order By: Relevance
“…Prior observations and experiments demonstrated that adults recognize the presence of tadpoles in the pools and strongly avoid the pools containing predators and heterospecific competitors (Brown et al 2008b). Our experiments revealed that D. variabilis males prefer pools with unrelated eggs and actively deposit their tadpoles within these pools.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Prior observations and experiments demonstrated that adults recognize the presence of tadpoles in the pools and strongly avoid the pools containing predators and heterospecific competitors (Brown et al 2008b). Our experiments revealed that D. variabilis males prefer pools with unrelated eggs and actively deposit their tadpoles within these pools.…”
Section: Discussionsupporting
confidence: 52%
“…Dendrobates imitator, a related species of poison frog that can occur sympatrically with D. variabilis in Peru, exhibits biparental care and trophic egg feeding of tadpoles in the context of monogamous pair bonds (Brown et al 2008a). Field experiments have demonstrated that D. variabilis tadpoles typically kill and consume D. imitator tadpoles if they are placed in the same pool (Brown et al 2008b). Hence, if a male D. variabilis were able to place a tadpole into a pool used by a D. imitator pair for tadpole feeding, the D. variabilis tadpole would probably eliminate the D. imitator tadpole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Although both males and females in this population have a yellow-green spotted aposematic phenotype, males are more engaged in territorial behavior, and therefore are likely the most visible to predators and researchers (Brown et al, 2008a), a trait common amongst dendrobatids (Prö hl, 2005). Many male behaviors, such as territory maintenance via calling, also reveal a male's location to potential predators.…”
Section: Methodsmentioning
confidence: 94%
“…Bromeliad morphological traits are generally chosen by anurans based on diverse ecological requirements such as parental care, food availability, predator avoidance, or to reduce competition (e.g. Brown et al 2008, Poelman et al 2013, Ryan & Barry 2011. Amphibians have differing degrees of association with bromeliads (e.g.…”
Section: Introductionmentioning
confidence: 99%